Peran Radio Al-Hikmah Dalam Pendidikan Di Pondok Pesantren Imam Asy-Syafi’i Genteng Banyuwangi - Zen, Iris Agripina; Mia Hasanah Amanah Illahi; Pratama, Repaldy Ananditasyah; Anwar, Saepul (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to explore the role of Radio Al-Hikmah as an educational medium at Imam Asy-Syafi’i Islamic Boarding School in Genteng, Banyuwangi. A qualitative method with a narrative approach was employed, gathering data through observation, in-depth interviews, and documentation. The findings reveal that Radio Al-Hikmah plays a strategic role in supporting non-formal education, particularly in character building and promoting Islamic values among students and the broader community. Broadcast content is managed collaboratively by teachers and students, featuring programs such as religious lectures, hadith memorization, and educational children's segments. Despite its great potential, the radio faces several challenges including limited resources, social pressures, and the need for careful content editing to maintain moderation and inclusivity. The study recommends strengthening broadcast management and enhancing student involvement in the development of educational media within the pesantren environment.